Durable disorder understanding the politics of Northeast India - Baruah, Sanjib (New Delhi ; Oxford : Oxford University Press, 2007)
These essays on the politics of insurgency-ridden northeast India show how counter-insurgency operations have virtually led to the establishment of a de facto authoritarian military rule.
Originally published: 2005.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Government, Resistance to -- India, Northeastern; India, Northeastern -- Politics and government -- 19th century; India, Northeastern -- Politics and government -- 20th century; India, Northeastern -- Ethnic relations